(1634) حول مفاهيم ومؤشرات اقتصاد المعرفة : عرض لبعض التجارب الدولية مع الإشارة لحالة مصر. On the concepts and indicators of the knowledge economy: A presentation of some international experiences with reference to the case of Egypt - الريس، أماني. (القاهرة : معهد التخطيط القومي،, 2018)
سبتمبر 2007.